Mycoplasma hyorhinis and Mycoplasma hyosynoviae dual detection patterns in dams and piglets - Roos, Luiza R. (PLoS One, 2019)
Mycoplasma hyorhinis and M. hyosynoviae are agents associated with arthritis in pigs. This study investigated the tonsillar detection patterns of M. hyorhinis and M. hyosynoviae in a swine population with a history of lameness. The plausibility of dual PCR detection of these agents in dams at one and three weeks post-farrowing and their offspring at the same time was determined. The association between M. hyorhinis and M. hyosynoviae detection in piglets and potential development of lameness in wean-to-finish stages was evaluated by correlating individual piglet lameness scores and PCR detection in tonsils. Approximately 40% of dams were detected positive for M. hyorhinis and M. hyosynoviae at both one and three weeks post-farrowing. In first parity dams, M. hyorhinis was detected in higher proportions (57.1% and 73.7%) at both weeks of sampling compared to multi-parity dams. A lower proportion of first parity dams (37.5%) were detected positive at week one with M. hyosynoviae and an increase in this proportion to 50% was identified in week three. Only 8.3% of piglets were detected positive for M. hyorhinis in week one compared to week three (50%; p<0.05). The detection of M. hyosynoviae was minimal in piglets at both weeks of sampling (0% and 0.9%). Lameness was scored in pigs 5–22 weeks of age, with the highest score observed at week 5. The correlation between PCR detection and lameness scores revealed that the relative risk of developing lameness post-weaning was significantly associated with detection of M. hyorhinis in piglets at three weeks of age (r = 0.44; p<0.05).The detection pattern of M. hyorhinis and M. hyosynoviae in dams did not reflect the detection pattern in piglets. Results of this study suggest that positive detection of M. hyorhinis in piglets pre-weaning could act as a predictor for lameness development at later production stages.